Peranan Gaya Kepemimpinan dan Pengambilan Keputusan dalam Meningkatkan Prestasi Kerja di Kembali Villas - Azhmy, Muhammad Fauzan (Universitas Harapan Medan, 2025)
The company's success in achieving its goals can be seen by the presence of high work performance. The main thing that companies need is the role of a leader who is able to apply good leadership to build relationships and collaboration in every element of the company. This research was conducted at Kembali Villas with the aim of knowing the leadership style applied and its role in improving work performance. Research using qualitative methods with observation and interviews. One of the fundamental factors is leadership style, a leader must first get to know the employees before applying his leadership style. The result of the research is that the leadership style used by Kembali villas is a democratic leadership style, it can be seen that the leader always provides an open opportunity for employees to provide opinions and solutions regarding the conditions of Kembali villas. This leadership style is able to improve the work performance of the employees of Kembali Villas.